Tinjauan Hukum Terhadap Penjualan Aplikasi Berbayar Dengan Cara Pinjam Akun Pribadi (Apple ID) - ika ramadhani (UIR Press, 2018)
The research was aimed at knowing the validity of the sales of paid apps by lending personal account (Apple ID) based on software lisence and the legal impact of selling paid apps by lending personal account (Apple ID). The research was a normative legal research. The approach used were statutory and conceptual approaches. Legal source used were primary, secondary, tertiary legal resources. Legal sources were collected by using literature study supplemented with interview. The collected legal sources were analyzed qualitatively. The research results indicate that the sales of paid apps by lending personal account (Apple ID) based on software lisence constitutes an illegal act because there is no right use transfer between Apple as the provider of apps that are available in App Store to the owner of Apple ID as the user of the application. The legal impact of the sales of paid apps by lending personal account constitutes branch of a contract which can be asked for liability based on Article 32 Law No 11 of 2008 concerning Information Electronic Transactions, Law No 28 of 2014 corcerning Copyright. And Terms and Condition provided by Apple Inc.The research was aimed at knowing the validity of the sales of paid apps by lending personal account (Apple ID) based on software lisence and the legal impact of selling paid apps by lending personal account (Apple ID). The research was a normative legal research. The approach used were statutory and conceptual approaches. Legal source used were primary, secondary, tertiary legal resources. Legal sources were collected by using literature study supplemented with interview. The collected legal sources were analyzed qualitatively. The research results indicate that the sales of paid apps by lending personal account (Apple ID) based on software lisence constitutes an illegal act because there is no right use transfer between Apple as the provider of apps that are available in App Store to the owner of Apple ID as the user of the application. The legal impact of the sales of paid apps by lending personal account constitutes branch of a contract which can be asked for liability based on Article 32 Law No 11 of 2008 concerning Information Electronic Transactions, Law No 28 of 2014 corcerning Copyright. And Terms and Condition provided by Apple Inc.